K=3+5-2+6-(-5)

Simple and best practice solution for K=3+5-2+6-(-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for K=3+5-2+6-(-5) equation:


Simplifying
K = 3 + 5 + -2 + 6 + -1(-5)

Multiply -1 * -5
K = 3 + 5 + -2 + 6 + 5

Combine like terms: 3 + 5 = 8
K = 8 + -2 + 6 + 5

Combine like terms: 8 + -2 = 6
K = 6 + 6 + 5

Combine like terms: 6 + 6 = 12
K = 12 + 5

Combine like terms: 12 + 5 = 17
K = 17

Solving
K = 17

Solving for variable 'K'.

Move all terms containing K to the left, all other terms to the right.

Simplifying
K = 17

See similar equations:

| 11=2-3v | | 85=.5x(17) | | 15m-4(2m-6)=38 | | 3*3*3-(31-2*3)= | | -2(3-7x)=22 | | 15-7(x-2)=1 | | (2sin2x)/x | | u^2-32u+31=0 | | 10x+9(3)=8 | | 1/4d_ | | f(x)=ln(81sin^2x) | | 3+4x=13+9x | | 2a^3b^0/c^2)-3 | | An=n^2+3n | | Tan^2x-5tanx-6=0 | | 2y=-3x+8 | | -4(7x+1)=-312 | | -5=-20+-25 | | 12x^2-132x+252=0 | | 30=7+N-4+8 | | 40=-2(23-y)+3(y-3) | | -8=17+6z | | 6(x+6)=-9+3x | | 7=3(23-x)+2(x-2) | | 7=t^2-6t | | -3p-48=0 | | 3r+11=2-3(3r+3) | | -7+x=-3x+25 | | 3ln(5x+4)=22 | | 4(4x-9)-6=4(x-4)+46 | | 16x^2-7t=17t-9 | | 36-6x=14+5x |

Equations solver categories